Integrated IoT System for Real-Time Electrical Load Monitoring - Prasetyo, Yuli; Triwijaya, Santi; Khakim, Ainul; Prakoso, Dimas Nur; Winarno, Basuki (Geuthèë Institute, 2025)
The uncontrolled and excessive consumption of electrical energy, especially in households, often leads to significant energy waste. This issue adversely affects both consumers and electricity providers such as PLN. To address this problem, a system titled